Pengaruh Penggunaan Media Kartu terhadap Kemampuan Membaca Siswa Kelas I SDN 10 Lubuk Buaya Padang - Arief, Darnis (AT-TA'LIM, 2014)
Reading is one of the most important language skills in the Elementary School since it is a tool to learn other subjects.Â  It is so because whatever you learn, you will need reading skills.Â  However, several researches show that Elementary school studentsâ€™ reading competence were still low.Â  Therefore, the current research problem is addressed to answer the question: â€œIs there any impact of using cards to studentsâ€™ reading skill at Elementary School?â€Â  In line with the question, then, the study aims at investigating the impact of cards to first grade studentsâ€™ reading skills in the Elementary School.Â  As a quasi experimental research, the datum was collected through reading test.Â  The reliability of instrument was tested through split method, while content validity was applied to the whole content.Â  With the t-test, the research shows that the use of Cards gave significant impact to studentsâ€™ reading skill in the Elementary School.Â  Therefore, it is fair to suggest that teachers at Elementary school should use cards to teach students in early reading activity.CopyrightÂ Â©Â 2014Â by Al-Ta'limÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v21i1.68